The Construction of Authority in the Old English Judith - Jacek Olesiejko (Polish Journal of English Studies)
The present article investigates the representation of Judith, the protagonist of the Old English poem preserved in the Beowulf Manuscript, based on episodes from the Old Testament Book of Judith. It argues that Judith makes significant additions to the biblical source with the aim of presenting the heroine as a figure of wisdom and justice. It also argues that such a representation of Judith is significant given the historical context of the composition of the poem. If the poem was composed in tenth-century England during Viking invasions, the way the text crafts Judith as a figure of wisdom and good counsel is evocative of some political ideas circulating in poetic, homiletic texts as well as in the Anglo-Saxon Chronicle. The Chronicle’s representation of decision-making as a joint venture of the king and witan can especially help to elucidate the concept of authority presented in the poem, as Judith develops the antagonist Holofernes as an example of an ill-counselled and unwise leader, while depicting Judith as a figure of authority representing divine justice. The Judith poet manipulates the feast scene that he finds in the biblical source with a view to enhancing its representation of Holofernes as an example of unwisdom and bad counsel. Another significant addition to the source is the poem’s emphasis on Judith’s wisdom as well her physical and spiritual radiance. In fact, the poem’s manipulation of light imagery and its recurrent contrasting of wisdom with unwisdom reflects the pressing concerns of the era regarding hierarchy, authority, obedience, and faith, all of which came to be considered key concepts in the unification of an England in crisis. The poem’s imagery of light is directly linked to the poem’s theme of justice and wise action. The sustained imagery of light and radiance underlies the poet’s account of Judith’s violence as a performance of divine justice. The imagery of light also creates a structural connection with the account of the Bethulian army victory over the Assyrians in the second half of the poem, enhancing both the poem’s artistic unity and its political purpose.